Evaluation of Medication Planning with ABC-VEN Analysis at Indriati Solo Baru Hospital - Fiqri Zulpadly; Fiomitta Nur Aulia (Universitas Gadjah Mada, 2024)
Background: Implementation of ABC-VEN drug planning evaluation can improve the efficiency of drug stockpiles, reduce the risk of vacuum, and ensure optimal drug availability for patient care. Objectives: In this study, an evaluation of the 2021 drug plan was carried out at Indriati Solo Baru Hospital using ABC-VEN combination analysis to know the percentage proportions of each group as well as the characteristics of the drug. Methods: The type of research is descriptive analysis using quantitative data performed retrospectively. Primary data was used from direct interviews with the head of the pharmacy and logistics unit, as well as secondary information in terms of drug planning activities. Samples are data on drug planning, acquisition, and use in 2021. The data are then analyzed using the ABC-VEN method. Results: The results of the study show the percentage of drug items in groups A, B, and C at 13.28%, 20.68%, and 66.04%, with investment values of 69.99%, 19.99%, and 10.02%. Whereas in groups V, E, and N, there are 18.55%, 71.18%, and 10.28% with an investment value of 23.92%, 65.51%, and 10.57%. The evaluation results using the combination method ABC-VEN obtained drugs from the categories Priority (P), Main (M), and Supplementary (S), which are 148 items, 568 items, and 82 items. Conclusion: The use of ABC-VEN methods in drug stock evaluation is essential to accurately identify PMS medicines so that drug supply planning and management are more efficient and effective, as well as ensuring the availability of medicines that are optimally tailored to patient needs.